Critical events at critical times? A gendered identity approach on the path to (sustainable) leadership - Gloor, Jamie L.; Rehbock, Stephanie K.; Kark, Ronit (Frontiers in Psychology, 2023)
The early career phase is a key period of identity maintenance and change. But, it is also ripe with important, attention-grabbing occurrences (i.e., critical events) that may modify these processes, particularly influencing women’s leadership pursuit. Because previous research has overlooked if or how such events might alter identifying or if these processes differ for people who identify as men and women, we integrate the identity and critical events literatures to elaborate on how positive and negative critical events may shape men and women’s identifying in the work- and non-work domains over time. We propose that critical events’ effects on identity salience will occur both within and across domains, but that these effects will be stronger within (vs. across) domains. While both positive and negative events can exert negative effects on subsequent identity salience, we propose that the effects of critical events on identity salience may be stronger for women (vs. men). Finally, we connect work identity salience with subsequent leadership status, including contextual moderators that enhance or undermine these effects (i.e., inclusive organizational climate and mega-threats, respectively). We conclude with theoretical and practical implications of this research, including for workforce efficiency and social sustainability. We also highlight calls for future research stemming from our review (e.g., sustainability critical events and gendered analyses for [more] accurate science) as well as fruitful research areas and innovative practices at the work-nonwork interface for professionals on the path to leadership.